2014
DOI: 10.1186/s12245-014-0025-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations between in-hospital bed occupancy and unplanned 72-h revisits to the emergency department: a register study

Abstract: BackgroundA possible downstream effect of high in-hospital bed occupancy is that patients in the emergency department (ED) who would benefit from in-hospital care are denied admission. The present study aimed at evaluating this hypothesis through investigating associations between in-hospital bed occupancy at the time of presentation in the ED and the probability for unplanned 72-hour (72-h) revisits to the ED among patients discharged at index. A second outcome was unplanned 72-h revisits resulting in admissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…The entire 72-hour RV rate has been most commonly used for monitoring ED performance [4,5,23,44], but many of the RVs are caused by patient's factors such as worry about health or illness's factors such as disease progression rather than medical error [1,9,20,23], and several researchers suggested that the rate of RVA may be a better indicator for reflecting the quality of healthcare [3,45]. In this study, the 72-hour RVA rate was 0.9% of total ED visits, similar to the 0.5-1.5% reported in previous studies [1,11,20]. The proportion of RVA in total RV was 29.7%, which was higher than the admission rate of 24.0% in all ED patients.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The entire 72-hour RV rate has been most commonly used for monitoring ED performance [4,5,23,44], but many of the RVs are caused by patient's factors such as worry about health or illness's factors such as disease progression rather than medical error [1,9,20,23], and several researchers suggested that the rate of RVA may be a better indicator for reflecting the quality of healthcare [3,45]. In this study, the 72-hour RVA rate was 0.9% of total ED visits, similar to the 0.5-1.5% reported in previous studies [1,11,20]. The proportion of RVA in total RV was 29.7%, which was higher than the admission rate of 24.0% in all ED patients.…”
Section: Discussionsupporting
confidence: 84%
“…The number of boarding patients gradually increases from Monday to Friday, and then decreases on Friday afternoon. The median (IQR) value was 56 (44-68) for the total number of patients, 35 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) for the number of evaluating patients, and 14 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) for the number of boarding patients. Therefore, the third quartile, the critical point of overcrowding was 68, 44, and 26, for total, evaluating, and boarding indicators, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have suggested that hospital crowding not only causes boarding in the ED, but also that ED patients are less likely to be admitted to the hospital at times of access block and instead are discharged home [ 16 ]. Such admission-bias may reflect a strategy by which ED staff averts inpatient admission in all but the sickest patients [ 16 , 17 ]. Patients with acute abdominal pain frequently seek care in the ED and different management strategies have emerged for those lacking immediate indications for surgical treatment [ 18 ].…”
Section: Introductionmentioning
confidence: 99%